Modeling distributions and correlations in financial market returns. - Loh, Han Zhou. (2010)
The widely held models of Efficient Market Hypothesis were often shown to have shortcomings in explaining real life stock market fluctuations. In this paper, a short history of distribution models used in financial markets was briefly summarized. A simple approach was used to determine correlations in outliers of the markets. By proving correlations in market returns, it is shown to violate the fundamental assumptions of the Random Walk. As a result, the paper proposed a “Blind-tail” distribution which may possibly represent a better understanding of market distributions. Lastly, a simple empirical study using the principles of Chaos theory and non-linearity shows that market returns do display significant correlations.